Cross pathogenicity among isolates of Fusarium oxysporum causing wilt in cucumber and muskmelon - PRATIBHA SHARMA, MOUSA NAJAFINIA* and (Indian Phytopathology, 2009)
Fusarium wilt of vegetable crops is generally associated with the formae speciales of Fusarium oxysporum (Schlechtend: Fr.). Some isolates of F. oxysporum from India, obtained from wilted plants of cucumber (Cucumis sativus L) or melon (C. melo L), were pathogenic to cucumber (cultivars Long Green and Poinsette) melon and watermelon. One cultivar sponge gourd, two cultivars of bitter gourd (local and Long Coimbatore), Tomato were immune to all the 30 isolates of F.oxysporum tested. Strains of F. oxysporum from wilted cucumber or melon plants were highly pathogenic only to their original host species and were regarded as different formae speciales. Five of the tested isolates were pathogenic to both cucumber and melon, but cumulatively they were more aggressive on their original host, compared to other hosts tested. Disease symptoms of cross pathogenicity on melon plants were apparently less harmful and often expressed as growth retardation, but disease symptoms on cucumber plants were more destructive. It may be concluded that cucumerinum and melonis are the two distinct formae speciales. F. oxysporum f.sp. melonis should be considered a potential threat to cucumber crops.